2019
DOI: 10.1177/0954411919879250
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the primary stability of cementless acetabular cup implants on the biomechanical environment

Abstract: Biomechanical phenomena occurring at the bone–implant interface during the press-fit insertion of acetabular cup implants are still poorly understood. This article presents a nonlinear geometrical two-dimensional axisymmetric finite element model aiming at describing the biomechanical behavior of the acetabular cup implant as a function of the bone Young’s modulus Eb, the diametric interference fit ( IF), and the friction coefficient µ. The numerical model was compared with experimental results obtained from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(48 citation statements)
references
References 45 publications
6
40
2
Order By: Relevance
“…To achieve an optimal primary stability, a compromise should be found between: 1. reducing the relative micro-motions at the bone-implant interface (BII), 2. avoiding large gaps between bone and implant, which may lead to the formation of fibrous tissue in the peri-implant region [5], the formation of low-quality bone tissue or even inhibit bone growth [22,32,41], and 3. avoiding excessive stresses in peri-implant bone tissue, which may lead to bone necrosis or local ischemia [45]. All these phenomena may jeopardize osseointegration processes [22,38,42], and can lead to implant loosening. It remains difficult to predict ACI loosening because of its multi-factorial causes related to the implant properties, the cavity geometry (e.g., its diameter), and to the patient's bone quality [1,18,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve an optimal primary stability, a compromise should be found between: 1. reducing the relative micro-motions at the bone-implant interface (BII), 2. avoiding large gaps between bone and implant, which may lead to the formation of fibrous tissue in the peri-implant region [5], the formation of low-quality bone tissue or even inhibit bone growth [22,32,41], and 3. avoiding excessive stresses in peri-implant bone tissue, which may lead to bone necrosis or local ischemia [45]. All these phenomena may jeopardize osseointegration processes [22,38,42], and can lead to implant loosening. It remains difficult to predict ACI loosening because of its multi-factorial causes related to the implant properties, the cavity geometry (e.g., its diameter), and to the patient's bone quality [1,18,26].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, several numerical models have been developed to assess the biomechanical behavior of the cementless ACI with simplified bone geometries [17,38,46,54]. While such models offer some initial insight on the biomechanical parameters and the contact behavior of the BII in a controlled environment, their simplified geometry constitutes a strong limitation because it does not properly capture 3D effects that have an important influence on the structural behavior of the pelvis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, static [27,28] and dynamic [29] finite element models have been developed to understand the mechanical phenomena occurring during and after the AC implant insertion. Eventually, a cadaveric study showed that the instrumented impact hammer could be used in situations closed to the clinics in order to determine the AC implant primary stability [30].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the friction coefficient is important to understand the behaviour of the BII during and just after surgery and thus to prevent micromotion at the BII, which may cause implant failure. Moreover, the frictional behaviour is an important input parameter to be used in finite-element models [96,97] in order to model implant surgical procedures.…”
Section: Dedicated Implant Models To Measure Initial Mechanical Fixationmentioning
confidence: 99%